3D genome organisation in Drosophila. (3rd December 2019) - Moretti, Charlotte; Stévant, Isabelle; Ghavi-Helm, Yad
Abstract: Ever since Thomas Hunt Morgan's discovery of the chromosomal basis of inheritance by using Drosophila melanogaster as a model organism, the fruit fly has remained an essential model system in studies of genome biology, including chromatin organisation. Very much as in vertebrates, in Drosophila, the genome is organised in territories, compartments and topologically associating domains (TADs). However, these domains might be formed through a slightly different mechanism than in vertebrates due to the presence of a large and potentially redundant set of insulator proteins and the minor role of dCTCF in TAD boundary formation. Here, we review the different levels of chromatin organisation in Drosophila and discuss mechanisms and factors that might be involved in TAD formation. The dynamics of TADs and enhancer–promoter interactions in the context of transcription are covered in the light of currently conflicting results. Finally, we illustrate the value of polymer modelling approaches to infer the principles governing the three-dimensional organisation of the Drosophila genome.